Production of Low Emission Pellet from Coco Peat Waste - Alamsyah, Rizal; Siregar, Nobel Christian (International Coconut Community Journal, 2013)
Study was conducted on coco peat as a low emission pellet form biomass fuel alternative to produce synthetic gas (syngas) through gasification process in use for other processes. Coco peat was first screened and formulated with other materials such as coco peat, starch, and waste cooking oil. These materials were mixed and pelletized using a pelletizer to form coco peat pellet. It was burned on an updraft gasifier to produce synthetic gas (syngas) and then streamed to a stove through a pipe. The syngas was then split and burned and the heat generated was used for boiling water and for drying agricultural products. Air quality around the stove (emission test) was measured and analyzed when gasification took place. The best results of coco peat pellet were made from 85% of coco peat waste, 5% starch (binder), and 10% of waste cooking oil with stronger texture and shiny surface. The experimental gasification using updraft gasifier exhibited better result when half of the volume of gasifier was filled with 5 kg pellet and the syngas produced can be used for 3.5 hours drying and boiling. Air quality surrounding the stove was tested during gasification process. It was done based on the Indonesian Environmental Regulation issued by Indonesian the Ministry of Environment on Standards (KEP-13/MENLH/3/1995 dated March 7th, 1995) regarding standard air quality from static matter and covers NH3, Cl2, HCl, HF, NO2, particles, SO2 and H2S parameters. The result of measurements indicated that all parameters meet the quality standards) including CO and CO2 at 0.0001 mg/kg.